Molecular aspects of Omicron, vaccine development, and recombinant strain XE: A review - K, Akash; Sharma, Avinash; Kumar, Deepak; Singh, Sachin K.; Gupta, Gaurav; Chellappan, Dinesh K.; Dua, Kamal; Nagraik, Rupak (Journal of medical virology, 2022)
The global pandemic of COVID‐19 began in December 2019 and is still continuing. The past 2 years have seen the emergence of several variants that were more vicious than each other. The emergence of Omicron (B.1.1.529) proved to be a huge epidemiological concern as the rate of infection of this particular strain was enormous. The strain was identified in South Africa on November 24, 2021 and was classified as a “Variant of Concern” on November 26, 2021. The Omicron variant possessed mutations in the key RBD region, the S region, thereby increasing the affinity of ACE2 for better transmission of the virus. Antibody resistance was found in this variant and it was able to reduce vaccine efficiency of vaccines. The need for a booster vaccine was brought forth due to the prevalence of the Omicron variant and, subsequently, this led to targeted research and development of variant‐specific vaccines and booster dosage. This review discusses broadly the genomic characters and features of Omicron along with its specific mutations, evolution, antibody resistance, and evasion, utilization of CRISPR‐Cas12a assay for Omicron detection, T‐cell immunity elicited by vaccines against Omicron, and strategies to decrease Omicron infection along with COVID‐19 and it also discusses on XE recombinant variant and on infectivity of BA.2 subvariant of Omicron.